Quantile regression analysis of language and interpregnancy interval in Quebec, Canada - Nathalie, Auger (Health Promot Chronic Dis Prev Can, 2018)
INTRODUCTION: Short and long interpregnancy intervals are associated with adverse perinatal outcomes such as miscarriage and preterm delivery, but cultural differences in interpregnancy intervals are understudied. Identifying cultural inequality in interpregnancy intervals is necessary to improve maternal-child outcomes. We assessed interpregnancy intervals for Anglophones and Francophones in Quebec. METHODS: We obtained birth records for all infants born in Quebec, 1989−2011. We identified 571 461 women with at least two births, and determined the interpregnancy interval. We defined short interpregnancy intervals (< 18 months) as the 20(th) percentile of the distribution, and long intervals (≥ 60 months) as the 80(th) percentile. Using quantile regression, we evaluated the association of language with short and long intervals, adjusted for maternal characteristics. We assessed differences over time and by maternal age for disadvantaged groups defined as no high school diploma, rural residence, and material deprivation. RESULTS: In adjusted regression models, Anglophones who had no high school diploma had intervals that were 1.0 month (95% CI: −1.5 to −0.4) shorter than Francophones at the 20(th) percentile of the distribution, and 1.9 months (−0.5 to 4.3) longer at the 80(th) percentile. Results were similar for Anglophones in rural and materially deprived areas. The trends persisted over time, but were stronger for women < 30 years. There were no differences between advantaged Anglophones and Francophones. CONCLUSION: Disadvantaged Anglophones are more likely to have short and long interpregnancy intervals relative to Francophones in Quebec. Public health interventions to improve perinatal health should target suboptimal intervals among disadvantaged Anglophones.